N-point free energy distribution function in one dimensional random directed polymers - Dotsenko, V. (Condensed Matter Physics, 2014)
Explicit expression for the N-point free energy distribution function in one dimensional directed polymers in a random potential is derived in terms of the Bethe ansatz replica technique. The obtained result is equivalent to the one derived earlier by Prolhac and Spohn [J. Stat. Mech., 2011, P03020].